ANALISIS YURIDIS KERJASAMA ANTARA INTERNATIONAL CRIMINAL POLICE ORGANIZATION DENGAN KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM MELAKUKAN PENCARIAN DAN PENANGKAPAN PELAKU TINDAK PIDANA KORUPSI YANG MELARIKAN DIRI KE LUAR NEGERI - Nadia Yuri Malinda; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The criminal act of corruption is considered an extraordinary crime, evencorruption in Indonesia is now considered to be no longer a domestic issue, but hasbecome a cross border or transnational crime. The attempt to escape abroad is a modecomitted by corruption actor to avoid legal process. Generally the targeted countriesare countries that do not yet have an extradition treaty with Indonesia. As internationalcrime grows, the police in many parts of the world can not work alone, therefore thecooperation between the police and Interpol has an important role to capture andrepatriate fugitives who fled abroad. The purpose of this research are; first, to know theauthority that ICPO-Interpol has in cooperating with the Police State of The Republicof Indonesia to conduct searches and arrests of corrupt criminals who escaped abroad.Secondly, to find out if ICPO-Interpol can help catch fugitives who escaped to a countrythat does not have an extradition treaty with Indonesia. The type of research conductedis the normative legal research or literature, because the library material as the mainfocus in conducting research. This research is descriptive, that is a research describingclearly and detail about a problem.From the results of research problems there are two main things that can beconcluded. First, the authority of ICPO-Interpol in cooperation with the Police is toissue Notices sent by the Police through NCB-Interpol Indonesia and forward it to eachmember country. Secondly, Interpol can assist in returning fugitives escaped to othercountries that have no extradition treaty with Indonesia with Disguised Extradition orHanding Over, Mutual Legal Assistance (MLA) or through the police to police. Myadvice, first, Interpol cooperation in overcoming international crime more developed byadding member countries, for cooperation in handling international crime andtransnational crime become more effective. Secondly, Indonesia needs to improve andstrengthen the diplomatic network with other countries in the world to assist insupporting the performance of NCB-Interpol Indonesia.